STRATEGI MANAJEMEN STAFT HOTEL DALAM PELAYANAN UNTUK MENINGKATKAN KEPUASAN TAMU - Ni Putu Putri Indah Pertiwi; Ni Made Erin Prabayanti; I Gusti Ayu Melistyari Dewi (PT. Hafasy Dwi Nawasena, 2023)
The hospitality industry, as the backbone of tourism, places staff management as a key element of operational and service success. This article reviews strategies and best practices in hotel staff management, exploring how to create a work environment that enhances productivity, maintains a balance between staff needs and guest satisfaction, and deals with the changing dynamics of the industry. Through a holistic approach, hotels are expected to optimize work team performance, including skills development, innovative training, and a motivating work environment. The research methodology used a qualitative approach with in-depth literature analysis. The results underscore the crucial role of staff management in creating a solid foundation for operational success and guest satisfaction in the competitive hospitality industry.